2021
DOI: 10.1161/circresaha.120.318437
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA ZNF593-AS Alleviates Contractile Dysfunction in Dilated Cardiomyopathy

Abstract: Rationale: Previously, we identified the human cardiac long non-coding RNAs (lncRNAs) profile in dilated cardiomyopathy (DCM) patients, among which ZNF593-AS, also named as RP11-96L14.7 and ENST00000448923.2, showed good conservation among species. Objective: We aim to elucidate the mechanism underlying lncRNA in DCM and DCM that lead to heart failure, which might provide new insights into the mechanisms of DCM and possible treatment strategies in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 64 publications
(67 reference statements)
0
25
0
1
Order By: Relevance
“…HL-1 cells were cultured in Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 10% fetal bovine serum (FBS) in a humidified atmosphere of 95% air and 5% CO 2 at 37°C, as described previously ( Fan et al., 2021 ). Cells were treated with CVB3 (1 × 10 4 plaque forming unit) and collected 24 h later.…”
Section: Methodsmentioning
confidence: 99%
“…HL-1 cells were cultured in Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 10% fetal bovine serum (FBS) in a humidified atmosphere of 95% air and 5% CO 2 at 37°C, as described previously ( Fan et al., 2021 ). Cells were treated with CVB3 (1 × 10 4 plaque forming unit) and collected 24 h later.…”
Section: Methodsmentioning
confidence: 99%
“…Most of these functions are exerted by binding of the lncRNA to proteins, such as transcription factors, chromatin modifiers and other functional proteins. In the last decade, an increasing number of studies indicate the crucial roles of lncRNAs in development and diseases, including ageing and CVDs 9–14 . Our previous studies also revealed that lncRNA could directly bind to target protein, exerting effects on calcium homeostasis and electrical conduction in myocardial infarction and arrhythmia, respectively 13,15–17 .…”
Section: Introductionmentioning
confidence: 96%
“…In the last decade, an increasing number of studies indicate the crucial roles of lncRNAs in development and diseases, including ageing and CVDs. [9][10][11][12][13][14] Our previous studies also revealed that lncRNA could directly bind to target protein, exerting effects on calcium homeostasis and electrical conduction in myocardial infarction and arrhythmia, respectively. 13,[15][16][17] In cardiovascular senescence, lncRNAs are arising as a new frontier for treatment therapy.…”
mentioning
confidence: 97%
“…One study found that ROS levels promotes AF via increased intracellular Ca 2+ release by oxidized RyR2 (6). A recent research found that long non-coding RNA ZNF593-AS facilitated RyR2 mRNA stability (7). The changes in epigenetic state induced by ROS levels could provide the basis for uncovering the pathophysiology and management of AF.…”
Section: Introductionmentioning
confidence: 99%